PEMBERDAYAAN LITERASI DIGITAL DI DESA KALIKOA - Siti Ayu Ikasari; Muthli’ah; Ashim; Achmad Nurjannah (UI Cirebon (Universitas Islam Cirebon), 2023)
This research was conducted in Kalikoa Village with the aim of having skills (life skills) which not only involve the ability to use technology, information, and communication devices, but also social skills, learning abilities, and have attitudes, critical thinking, creative, and inspirational as digital competence. Therefore, efforts to empower digital literacy need to be made to increase public awareness of the importance of digital literacy in everyday life. The problem that becomes the background of this research is that people do not understand the importance of digital literacy so that people are easily influenced by hoax news, lack of expertise in evaluating and digesting information critically so that they still do not use technology wisely. The community service method is carried out to empower digital literacy in Kalikoa Village during the KKM (Student Work Class) activity which lasts for a month. Sources of research data in the form of observations, interviews and document studies. The results of the study show that digital literacy will create a society with a critical-creative mindset and view. So, they will not be easily fooled by digital-based ones such as being victims of hoax information. In addition, understanding digital literacy can also help people to improve the economic and educational aspects in their daily life following the times critically and wisely.